Tailoring Organic LEDs for Bidirectional Optogenetic Control via Dual‐Color Switching. (2nd December 2021) - Ciccone, Giuseppe; Meloni, Ilenia; Fernandez Lahore, Rodrigo G.; Vierock, Johannes; Reineke, Sebastian; Kleemann, Hans; Hegemann, Peter; Leo, Karl; Murawski, Caroline
Abstract: Revealing the intricate logic of neuronal circuits and its connection to the physiopathology of living systems constitutes a fundamental question in neuroscience. Optogenetics offers the possibility to use light of specific wavelengths to study the activity of neurons with unprecedented spatiotemporal resolution. To make use of this technique at its full potential, bidirectional proteins may be expressed across the neuronal membrane to provoke both enhancement and inhibition of neuronal activity depending on the excitation wavelength. This generates the demand for light sources with high spatial precision, high operation speed, and multi‐color emission from the same location. To meet these requirements, the design, realization, and characterization of organic light‐emitting diodes (OLEDs) are presented with switchable bicolor emission, exhibiting high irradiance and good efficiency. The OLEDs can switch between blue and red/green light upon changing the voltage polarity, triggering both optogenetic inhibition and excitation in ND7/23 cells and Drosophila melanogaster larvae expressing bidirectional optogenetic proteins. This work shows the potential of engineering OLEDs to enable multicolor optogenetics with a single, organic device, and provides a new avenue towards bicolor optical brain stimulation in vivo. Abstract : Stacked organic light‐emitting diodes (OLEDs) that emit two different colors depending on the polarity of the applied voltage are tailored to stimulate tandem photosensitive proteins. As a result, the OLEDs successfully control ion currents in optogenetically modified ND7/23 cells and activate and inhibit motoneurons in Drosophila melanogaster larvae.